Mapping the risk of introduction of highly pathogenic avian influenza to Swedish poultry - Stiles, Pascale; Grant, Malin; Kim, Hyeyoung; Comin, Arianna; Svensson, Mikael; Nilsson, Johan; Nöremark, Maria (Preventive veterinary medicine, 2024)
Outbreaks of highly pathogenic avian influenza (HPAI) have resulted in severe economic impact for national governments and poultry industries globally and in Sweden in recent years. Veterinary authorities can enforce prevention measures, e.g. mandatory indoor housing of poultry, in HPAI high-risk areas. The aim of this study was to conduct a spatiotemporal mapping of the risk of introduction of highly pathogenic avian influenza virus (HPAIV) to Swedish poultry from wild birds, utilising existing data sources. A raster calculation method was used to assess the spatiotemporal risk of introduction of HPAIV to Swedish poultry. The environmental infectious pressure of HPAIV was first calculated in each 5km by 5km cell using four risk factors: density of selected species of wild birds, air temperature, presence of agriculture as land cover and presence of HPAI in wild birds based on data from October 2016-September 2021. The relative importance of each risk factor was weighted based on opinion of experts. The estimated environmental infectious pressure was then multiplied with poultry population density to obtain risk values for risk of introduction of HPAIV to poultry. The results showed a large variation in risk both on national and local level. The counties of Skåne and Östergötland particularly stood out regarding environmental infectious pressure, risk of introduction to poultry and detected outbreaks of HPAI. On the other hand, there were counties, identified as having higher risk of introduction to poultry which never experienced any outbreaks. A possible explanation is the variation in poultry production types present in different areas of Sweden. These results indicate that the national and local variation in risk for HPAIV introduction to poultry in Sweden is high, and this would support more targeted compulsory prevention measures than what has previously been employed in Sweden. With the current and evolving HPAI situation in Europe and on the global level, there is a need for continuous updates to the risk map as the virus evolves and circulates in different wild bird species. The study also identified areas of improvement, in relation to data use and data availability, e.g. improvements to poultry registers, inclusion of citizen reported mortality in wild birds, data from standardised wild bird surveys, wild bird migration data as well as results from ongoing risk-factor studies.